Permanent roommates in the transparent blockchain ecosystem - Grigoriadou, Valentini; Koskinas, Konstantinos (Homo Virtualis, 2023)
In this article we present the interpretation of the results of a qualitative research conducted in 2022 as part of a doctoral thesis, the subject of which is the socio-psychological implications, caused by the application of the innovative blockchain technology in education and in our society in general. For the needs of this research, an experimental application for degree certification was created. Through its extensive use, the participants formed elaborate opinions based on their experiential interaction with blockchain technology. This study drew on semi-structured in-depth interviews. Data were collected from fourteen contemporary citizens with the scientific capacity of political and social studies. This research is a flash of illumination in the relationships developed between the members of the university community and the relationships beyond it, focusing on the main features of blockchain technology, security, immutability, traceability, availability, integrity, absence of a central authority, privacy, shifting security to the end user and possible use of tokens. The reflexive thematic analysis led to the construction of a more general theme: "Blockchain will form what we will be in the future" which captures how the participants perceive the future reality filtered through the differentiated needs of each of one’s multiple identities. Two main themes were constructed under the overarching theme. Those two are: “blockchain as the Trojan horse of authorities and governing power” and “blockchain as the deus ex machina for modern man”. The adoption of blockchain technology as a tool to facilitate and simplify standard processes, meets the individual’s need for validity, transparency, meritocracy, fairness and the emergence of truth. At the same time, participants express intense concern about the possibility of blockchain being instrumentalized as a new form of power in conjunction with new technologies such as 5G, AI, cloud computing, IoT and BDAA. The results of the research demonstrate the thorough attention that needs to be given to the conditions, in which the application of blockchain technology will be implemented in the field of education, in order to have the acceptance of the whole university community and society.